2016
DOI: 10.1287/mnsc.2015.2324
|View full text |Cite
|
Sign up to set email alerts
|

Spillovers from Wiring Schools with Broadband: The Critical Role of Children

Abstract: Providing broadband to schools can be an effective way to foster household Internet adoption in neighboring areas. On the one hand, the infrastructure put into place to meet schools' needs can also serve households. On the other hand, students get acquainted with Internet at school and signal its usefulness to adults at home who, consequently, can be more likely to adopt it. In this paper we model the roles that broadband use at school and Internet adoption in neighboring households play in the decision to ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…5 An important strand of the literature analyzes the effects of ICT in school settings. Most of this previous work uses experimental and quasiexperimental methods, finding mixed results but typically no consistent impacts on math or reading educational achievement (Angrist & Lavy, 2002;Rouse & Krueger, 2004;Goolsbee & Guryan, 2006;Machin et al, 2007;Belo et al, 2014Belo et al, , 2016Falck et al, 2018). Our study is different because we study the effects of broadband access at home.…”
Section: Introductionmentioning
confidence: 94%
“…5 An important strand of the literature analyzes the effects of ICT in school settings. Most of this previous work uses experimental and quasiexperimental methods, finding mixed results but typically no consistent impacts on math or reading educational achievement (Angrist & Lavy, 2002;Rouse & Krueger, 2004;Goolsbee & Guryan, 2006;Machin et al, 2007;Belo et al, 2014Belo et al, , 2016Falck et al, 2018). Our study is different because we study the effects of broadband access at home.…”
Section: Introductionmentioning
confidence: 94%
“…The findings of this study confirmed our hypothesis that student ICT use intensity moderated the links of all three types of ICT use and their reading literacy, which is consistent with the research of (Gubbels et al, 2020) This similar effect pattern across ICT use intensity can be explained as follows. The positive effects of low ICT use on reading literacy can be explained by the fact that the original introduction of the computer and broadband enabled student access to more useful resources and provided helpful and interesting functions that attracted students' attention to learning (Barrow et al, 2009;Belo et al, 2016). With the increasing intensity of ICT use, and as ICT tools were expanded to be used in wider areas and in diverse ways, such as for leisure or social activities, student attention begins to be distracted from learning to some degree (Leuven et al, 2007).…”
Section: The Moderation Of Information and Communication Technologies...mentioning
confidence: 99%
“…The positive effects were also found in literature that have explored specific ICT tools’ influence on students’ learning. For example, studies by Barrow et al (2009) and Belo et al (2016) found that students who used computer programs performed better in reading than those who were exposed to traditional teaching methods. Grimes and Warschauer (2008) and Lai et al (2015) indicated that the use of ICT devices in the classroom can improve student academic performance in English and math at the end of 2 years of their participation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Financial education has proven to be very effective to both increase financial knowledge and positively affect financial choices (14). Virtually all governments that have developed a financial inclusion strategy have included financial education as a key component.…”
Section: Introductionmentioning
confidence: 99%